Domestication of the Euro Crisis: Legal and Political Manifestations of Euroscepticism in Germany - Nicole Scicluna (Journal of Contemporary European Research, 2014)
The euro crisis points towards the limits of the post-war pro-European integration consensus in Germany, a trend that has manifested itself in both the legal and political realms. In the legal arena, the powerful German Constitutional Court (GCC) has heard complaints on several key rescue measures, including the European Stability Mechanism (ESM) and the European Central Bank’s (ECB) bond buying programme. The Court’s ruminations on these initiatives both reflect and feed German eurosceptics’ concerns. They also have implications for the Eurozone as a whole, insofar as they limit the German government’s room to manoeuvre. In the political arena, a new eurosceptic party, Alternative für Deutschland (AfD), contested the September 2013 federal election and the May 2014 European parliamentary election, winning a handful of seats in the latter. AfD’s emergence potentially marks a shift towards a more overtly eurosceptical political discourse in Germany. Thus, both legal and political developments have the potential to constrain the choices for the EU as a whole by reconfiguring the political and policy landscape of Germany, the Union’s reluctant hegemon.